Recommendations of the Russian Gastroenterological Association on Clinical Use of High-Resolution Manometry in Diagnosis of Esophageal Disorders - V. T. Ivashkin; I. V. Mayev; A. S. Trukhmanov; O. A. Storonova; S. A. Abdulkhakov; D. N. Andreev; D. S. Bordin; E. R. Valitova; I. L. Klyaritskaya; V. V. Krivoy; Yu. A. Kucheryavyi; T. L. Lapina; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2020)
Aim. Current recommendations of the Russian Gastroenterological Association on clinical use of high-resolution manometry in diagnosis of esophageal disorders are intended to assist in clinical decision making, terminology standardisation and interpretation of clinical data.Key points. In 2018, a joint meeting of the Russian Gastroenterological Association and Russian Neurogastroenterology and Motility Group approved unified terminology and classification of esophageal motor function disorders for high-resolution manometry diagnosis.Gastrointestinal patient complaints typically concern esophageal disorders such as dysphagia, regurgitation, heart-burn, chest pain or belching. To exclude erosive and ulcerative lesions, eosinophilic esophagitis and organic changes, esophagogastroduodenoscopy and biopsy are recommended in pre-treatment. Upon excluding mucosal lesions and esophageal lumen obstruction as causal for symptoms, use of high-resolution manometry is recommended. This method of esophageal examination has become the “gold standard” in diagnosis of motor disorders.High-resolution manometry enables detailed investigation of integral quantitative and qualitative characteristics of esophagus motor function and specific related disorders, analysis of esophageal contractile propagation and strictly coordinated synchronous peristalsis of upper esophageal sphincter, esophagus and lower esophageal sphincter, which malfunction may provoke development of achalasia, esophagospasm, hiatal hernia, ineffective eso pha geal motility and other motor disorders.Conclusion. High-resolution manometry is a relatively new method for study of esophagus motor function gaining increasingly wide application in clinical practice. It enables a medical professional to obtain evidence that may critically affect the choice of optimal patient care strategy and effective treatment. Current recommendations are based on an extensive review of up-to-date information and will be updated with new corpus of clinical data and assessment emerging in evidential medicine to provide gastroenterologists country-wide with latest scientific and practical guidelines.